PENDAPAT KEPALA SEKOLAH DAN GURU PAMONG TENTANG KOMPETENSI PEDAGOGIK MAHASISWA PLP PGPAUD - Mashfufah, Syifa Rohmati; Setiasih, Ocih; Eliyawati, Cucu (Edukids: Jurnal Pertumbuhan, Perkembangan, dan Pendidikan Anak Usia Dini, 2016)
Principals  and  Mentor-Teachers’  Opinionson  The  Pedagogic Competence  Of  PGPAUD  FIP  UPI  Students  Taking  Professional  Internship Program  Academic  Year  2014-2015.  The  research  aims  to  find  the  opinions  of principals  and  mentor-teachers  on  the  pedagogic  competence  of  PGPAUD  FIP  UPI Students taking professional internship program in the academic year of 2014-2015. It adopted descriptive survey method. The population and sample of this research were all principals and mentor-teachers who supervised the professional internship program for 2014-2015 academic year. Data were collected using close-ended questionnaires as the instrument and were then analyzed with descriptive statistic.The principals’ opinion on the pedagogic competence of PGPAUDstudents taking professional internship program was  good  with  a  score  of  72.93%.  Mentor-teachers’  opinion  on  the  pedagogic competence of PGPAUD students taking professional internship program was good as well with a score of 62.06%. The research recommends that the instructional strategies used  in  improving  pedagogic  competence  be  more  applicative,  especially  for  the strategies used in teaching instructional evaluation, so that in addition to being able to identify  concepts  of  instructional  evaluation,  students  can  practice  applying  the techniques  in  the  field.  Future  research  is  suggested  to  raise  issues  on  pedagogic competence in the study program of Early Childhood Teacher Education in Indonesia to reveal further results and findings.The study program of Early Childhood Education is  recommended  to  create  more  competent  graduates  of  early  childhood  education teachers. Pendapat  Kepala  Sekolah  dan  Guru  Pamong  tentang  Kompetensi Pedagogik  Mahasiswa  PLP  PGPAUD  FIP  UPI  Tahun  Akademik  2014-2015. Tujuan  penelitian  ini  adalah  untuk  mengetahui  pendapat  kepala  sekolah  dan  guru pamong  tentang  kompetensi  pedagogik  mahasiswa  PLP  PGPAUD  FIP  UPI  tahun akademik 2014-2015. Metode yang digunakan survei deskriptive. Populasi dan sampel pada  penelitian  ini  adalah  seluruh  kepala  sekolah  dan  guru  pamong  yang  menjadi pembimbing  program  PLP  tahun  akademik  2014-2015.  Alat  pengumpulan  data penelitian ini menggunakan angket tertutup yang kemudian dianalisis dengan statistika deskriptif. Kepala sekolah  berpendapat tentang kompetensi pedagogik mahasiswa PLP PGPAUD adalah baik dengan nilai 72,93%. Pendapat guru pamang tentang kompetensi pedagogik  mahasiswa PLP PGPAUD adalah baik dengan nilai 62,06%. Rekomendasi penelitian  ini  agar  strategi  pembelajaran  yang  digunakan  dalam  meningkatkan kompentensi  pedagogik  lebih  aplikatif,  khususnya  untuk  strategi  pembelajaran matakuliah  evaluasi  pembelajaran,  sehingga  mahasiswa  selain  dibekali  pengetahuan mengenai konsep-konsep evaluasi pembelajaran, mahasiswa juga dapat berlatih untuk menggunakan  teknik-teknik  penilaian  di  lapangan  secara  langsung.  Untuk  penelitian selanjutnya  agar  dapat  mengangkat  permasalahan  mengenai  kompetensi  pedagogik pada program studi PGPAUD di Indonesia sehingga diharapkan peneliti mendapatkan temuan  baru  dan  memberikan  rekomendasi  untuk  program  studi  PGPAUD  dan menghasilkan lulusan-lulusan guru PAUD yang lebih baik lagi.